Ordered Nanomaterial Thin Films via Supported Anodized Alumina Templates - Es-Souni, Mohammed; Habouti, Salah (Frontiers in Materials, 2014)
Supported anodized alumina template films with highly ordered porosity are best suited for fabricating large area ordered nanostructures with tunable dimensions and aspect ratios. In this paper we first discuss important issues for the generation of such templates, including required properties of the Al/Ti/Au/Ti thin film heterostructure on a substrate for high quality templates. We then show examples of anisotropic nanostructure films consisting of noble metals using these templates, discuss briefly their optical properties and their applications to molecular detection using surface enhanced Raman spectroscopy. Finally we briefly address the possibility to make nanocomposite films, exemplary shown on a plasmonic-thermochromic nanocomposite of VO2-capped Au-nanorods.